Vulnerability Concepts and its Application in Various Fields: A Review on Geographical Perspective - Paul, Shitangsu Kumar (Journal of Life and Earth Science, 2014)
Vulnerability has no universal definition. Experts from various disciplines use the concept and define vulnerability, which leads diverse measuring methods to serve their own purpose and interests. Approaches to define vulnerability vary among the disciplines because of the various components of risk, household response and welfare outcomes. The objective of this paper is to present an overview based on available scientific literature from various disciplines to examine the origin, evolution and use of the vulnerability concept across different field of studies. Vulnerability is exclusively used in various disciplines such as geography, anthropology, economics, ecology, public health, poverty and development, sustainable livelihoods, famine and food security, sustainability science, land management, disaster management and climate change. Therefore, different disciplines have their own reasons for defining, measuring and developing conceptual models of vulnerability; hence there is no reason to presume that concepts, measures and methods will be universal across the disciplines. Lessons learned from one area may not be equally suitable for all. Hence, differences between various fields need to be bridged by a holistic approach and multidisciplinary research cooperation, and geography as a unique multidisciplinary field of study has the major disciplinary legitimacy to fill up the gaps and to create a common platform to work together in vulnerability research among the various research traditions. DOI: http://dx.doi.org/10.3329/jles.v8i0.20150 J. Life Earth Sci., Vol. 8: 63-81, 2013